Implementasi Peraturan Daerah P4GN di Kota Pariaman - Putri Mawarni, Indah; Kusdarini, Kusdarini; Wahyuni, Nila (Jurnal Manajemen dan Ilmu Administrasi Publik (JMIAP), 2026)
This research aims to analyze the implementation of the regulation using the policy implementation framework proposed by Jan Merse, which includes the variables of information, policy content, community support, and distribution of resources. This study employs a descriptive qualitative approach. Data were collected through interviews and document analysis. The main informants consisted of seven individuals from the Pariaman City Office of National Unity and Politics, the Pariaman Police Resort, and the Mandatory Reporting Institution (IPWL) at Naras Public Health Center. Triangulation informants included eight individuals from local government officials, village heads, and community leaders. The documents analyzed comprised the BNN Strategic Plan 2020–2024, drug crime suspect data from the national to the city level, the Regional Action Plan (RAD) for P4GN 2023–2028, and Regional Regulation of Pariaman City Number 2 of 2023. The findings indicate that the implementation of the P4GN-PN regulation has been carried out but remains suboptimal. The decline in drug abuse and trafficking cases in 2023 was not significant, and several mandated activities have not been fully implemented, particularly direct community-level socialization across most villages and the limited dissemination of rehabilitation information by the IPWL. Uneven socialization efforts were concentrated in certain areas, while effective coordination with communities was mainly observed in villages that had established Anti-Drug Resilient Villages. These findings highlight that equitable information dissemination, strengthened community support, and expanded coordination are critical to improving the effectiveness of P4GN-PN policy implementation in Pariaman City.